2023
DOI: 10.7573/dic.2022-11-3
|View full text |Cite
|
Sign up to set email alerts
|

Non-small-cell lung cancer: how to manage BRAF-mutated disease

Abstract: BRAF mutations are reported in about 3–5% of non-small-cell lung cancer (NSCLC), almost exclusively in adenocarcinoma histology, and are classified into three different classes. The segmentation of BRAF mutations into V600 (class 1) and non-V600 (classes 2 and 3) relies on their biological characteristics and is of interest for predicting the therapeutic benefit of targeted therapies and immunotherapy. Given the relative rarity of this molecular subset of disease, evidence sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 114 publications
0
9
0
Order By: Relevance
“…Mitogen‐activated protein kinase inhibitors, such as trametinib, have been shown to cause pneumonitis induced by targeted molecular therapy. 4 Among targeted therapies for non‐small cell lung cancer, pneumonitis has been reported in 5% of patients with gefitinib, 4.5% with erlotinib, 0.7% with ALK inhibitors, such as crizotinib, ceritinib, and 6.5% with osimertinib therapy. 1 , 5 It has been also reported that 1.1% of patients using dabrafenib plus trametinib developed pneumonitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mitogen‐activated protein kinase inhibitors, such as trametinib, have been shown to cause pneumonitis induced by targeted molecular therapy. 4 Among targeted therapies for non‐small cell lung cancer, pneumonitis has been reported in 5% of patients with gefitinib, 4.5% with erlotinib, 0.7% with ALK inhibitors, such as crizotinib, ceritinib, and 6.5% with osimertinib therapy. 1 , 5 It has been also reported that 1.1% of patients using dabrafenib plus trametinib developed pneumonitis.…”
Section: Discussionmentioning
confidence: 99%
“…Given that the combination of radiotherapy and BRAF inhibitors for brain metastases of melanoma may increase cutaneous radiation‐induced reactions, 7 and the exclusion from a clinical trial of patients who had been treated with radiotherapy within 14 days, 3 BRAF inhibitors were started at least 2 weeks after SRT. Trametinib has been reported to cause interstitial lung disease in real‐world clinical practice, 4 accordingly, dabrafenib and trametinib combination therapy was initiated under PSL therapy, which did not worsen the interstitial pneumonitis. When the PSL dose was reduced to 8 mg, there was a worsening of symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…BRAFV600E mutations in NSCLC are more common in micropapillary patterns and females with no smoking history, while non- V600E BRAF mutations are more likely associated with mucinous patterns and males with a smoking history [ 2 ]. BRAF mutations are associated with metastasis to the central nervous system (CNS), especially with class II and III mutations [ 65 ]. In an analysis of BRAF -altered samples by Negrao et al, the most common BRAF mutations were missense mutations (90%, with 45% of which were variants of unknown significance), followed by nonsense and splice-site mutations (5% each) [ 64 ].…”
Section: Braf/mek Inhibitors Across Various Cancersmentioning
confidence: 99%
“…BRAF, located on chromosome 7, encodes a serine/threonine protein kinase 40 . In the context of NSCLC, BRAF mutations occur in ~1.5% to 3.5% of cases 41 .…”
Section: Pathogenesis Of Nsclcmentioning
confidence: 99%